Relevansi Kebijakan Merdeka Belajar Terhadap Konsep Pendidikan Tanpa Sekolah Ivan Illich - Achmad Subkhan (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2021)
Educational thought is an exciting theme of discourse to follow. This discourse is more enjoyable when it is associated with the level of success of education in Indonesia, according to the quality of human resources. Surveys on the quality of education, especially in the literacy aspect, show worrisome results. For example, the results of the Program for International Student Assessment (PISA) survey released on December 3, 2019, placed Indonesia at a meager score for three literacy areas; reading, math, and science. This concern is still compounded by the challenges of facing 21st-century skills, the era of the Industrial Revolution 4.0. This condition is the background of Merdeka Belajar's policy. The concept of Merdeka Belajar has long been alluded to by experts. For example, in a different perspective, Ivan Illich initiated the idea of deschooling society (deschooling education). This paper examines the relevance of Merdeka Belajar's policy to Ivan Illich's concept of deschooling education. The research sources are the documentation of Merdeka Belajar and the thoughts of Ivan Illich, as well as relevant library materials. Therefore it is a type of library research. The approach used is a qualitative approach by conducting content analysis. The study results show that there is no relevance between Merdeka Learning policy to the concept of deschooling education of Ivan Illich.